Educational Intervention Reduced Family Medicine Residents' Intention to Request Diagnostic Tests: Results of a Controlled Trial. (April 2021) - Schneider, Antonius; Bühner, Markus; Herzog, Therese; Laverty, Siona; Ziehfreund, Stefanie; Hapfelmeier, Alexander; Schneider, Dagmar; Berberat, Pascal O.; Roos, Marco; ,
Objective: Dealing with uncertainty is a core competence for physicians. To evaluate the impact of an educational intervention on family medicine residents' (FMRs') intention to request diagnostic tests and their attitudes toward uncertainty. Methods: Nonrandomized controlled trial. Intervention group (IG) FMRs participated in interactive "dealing with uncertainty" seminars comprising statistical lessons and diagnostic reasoning. Control group (CG) FMRs participated in seminars without in-depth diagnostic lessons. FMRs completed the Dealing with Uncertainty Questionnaire (DUQ), comprising the Diagnostic Action and Diagnostic Reasoning scales. The Physicians' Reaction to Uncertainty (PRU) questionnaire, comprising 4 scales (Anxiety Due to Uncertainty, Concern about Bad Outcomes, Reluctance to Disclose Uncertainty to Patients, and Reluctance to Disclose Mistakes to Physicians) was also completed. Follow-up was performed 3 months later. Differences were calculated with repeated-measures analysis of variance. Results: In total, 107 FMRs of the IG and 102 FMRs of the CG participated at baseline and follow-up. The mean (SD) Diagnostic Action scale score decreased from 24.0 (4.8) to 22.9 (5.1) in the IG and increased in the CG from 23.7 (5.4) to 24.1 (5.4), showing significant group difference ( P = 0.006). The Diagnostic Reasoning scale increased significantly ( P = 0.025) without a significant group difference ( P = 0.616), from 19.2 (2.6) to 19.7 (2.4) in the IG and from 18.1 (3.3) to 18.8 (3.2) in the CG. The PRU scale Anxiety Due to Uncertainty decreased significantly ( P = 0.029) without a significant group difference ( P = 0.116), from 20.5 (4.8) to 18.5 (5.5) in the IG and from 19.9 (5.5) to 19.0 (6.0) in the CG. Conclusion: The structured seminar reduced self-rated diagnostic test requisition. The change in Anxiety Due to Uncertainty and Diagnostic Reasoning might be due to an unspecific accompanying effect of the extra-occupational seminars for residents.